2021
DOI: 10.33988/auvfd.759964
|View full text |Cite
|
Sign up to set email alerts
|

The mandibles of the Honamli and Hair goat (Capra hircus); a geometric morphometric study

Abstract: The aim of the study was to analyze mandible of the Honamli and Hair goats according to the sex factor by geometric morphometric methods. A total of 36 adult goat mandibles including 9 males and 9 females for each breed, were used in the study. After the mandibles were photographed from the left lateral side, 10 homolog landmarks were marked. Generalized Procrustes, Relative Warp, and Principal Component Analysis were performed for the data of landmark coordinates. In the study, the first principal component e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In our study, the degree of dorsal separation of the skulls by race was limited. Demiraslan et al (2021), in their geometric morphometric study on the mandible of Honamlı and Hair goats, reported that Hair goats showed a very distinct gender difference compared to Honamlı goats, and that male goats were clearly clustered compared to female goats in terms of race factor. In our study, the degree of dorsal separation of skulls by breed was limited and the most prominent clustering was seen in Honamlı skulls in females and Honamlı and Saanen skulls in males.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the degree of dorsal separation of the skulls by race was limited. Demiraslan et al (2021), in their geometric morphometric study on the mandible of Honamlı and Hair goats, reported that Hair goats showed a very distinct gender difference compared to Honamlı goats, and that male goats were clearly clustered compared to female goats in terms of race factor. In our study, the degree of dorsal separation of skulls by breed was limited and the most prominent clustering was seen in Honamlı skulls in females and Honamlı and Saanen skulls in males.…”
Section: Discussionmentioning
confidence: 99%
“…However, thanks to geometric analysis, it could be interpreted in terms of shape. To determine the sexual dimorphism by geometric analysis in dogs, goats, and sheep, information was obtained in terms of geometric morphometry [21,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted to reveal the shape differences of cranium or mandible via the geometric morphometric method in different species such as wolf (11), dog (23), quail (30), turkey (10), sheep (6), goat (5), and deer (17). However, no study comparing two different sheep breeds via semilandmarks was encountered.…”
Section: Introductionmentioning
confidence: 99%